The Role of HR Analytics in Enhancing Organizational Performance: A Review Literature - Delfi Kurnia Zebua; Tomi Apra santosa; Fegid Dian Putra; Nanich Framulya (AKADEMI TEKNIK ADI KARYA, 2024)
The advent of Human Resource (HR) analytics has revolutionized the way organizations manage their workforce, enabling data-driven decision-making and strategic planning. This literature review aims to synthesize recent research on the role of HR analytics in enhancing organizational performance. By systematically analyzing studies published over the past decade, we identify key themes, methodologies, and findings that highlight the impact of HR analytics on various performance metrics. The review reveals that HR analytics contributes significantly to improving recruitment processes, employee retention, talent management, and overall organizational effectiveness. Moreover, the integration of advanced analytics tools and techniques, such as predictive modeling and machine learning, has been shown to provide deeper insights into employee behavior and organizational dynamics. Despite its benefits, the implementation of HR analytics faces several challenges, including data privacy concerns, the need for specialized skills, and resistance to change within organizations. This review concludes by discussing the implications for HR practitioners and offering recommendations for future research to address the existing gaps and further harness the potential of HR analytics in driving organizational success.